Akt: a key transducer in cancer - Tsai Pei-Jane; Lai Yi-Hsin; Manne Rajesh Kumar; Tsai Yau-Sheng; Sarbassov Dos; Lin Hui-Kuan (Springer Science and Business Media LLC, 2022)
Growth factor signaling plays a pivotal role in diverse biological functions, such as cell growth, apoptosis, senescence, and migration and its deregulation has been linked to various human diseases. Akt kinase is a central player transmitting extracellular clues to various cellular compartments, in turn executing these biological processes. Since the discovery of Akt three decades ago, the tremendous progress towards identifying its upstream regulators and downstream effectors and its roles in cancer has been made, offering novel paradigms and therapeutic strategies for targeting human diseases and cancers with deregulated Akt activation. Unraveling the molecular mechanisms for Akt signaling networks paves the way for developing selective inhibitors targeting Akt and its signaling regulation for the management of human diseases including cancer.
Keywords: PI3K, Akt, TRAF6, Skp2, Cancer, Posttranslational modifications, type of access: open access